Gene expression in the spinal cord in female lewis rats with experimental autoimmune encephalomyelitis induced with myelin basic protein. - Hayley R Inglis (Public Library of Science (PLoS), 2012)
Background Experimental autoimmune encephalomyelitis (EAE), the best available model of multiple sclerosis, can be induced in different animal strains using immunization with central nervous system antigens. EAE is associated with inflammation and demyelination of the nervous system. Micro-array can be used to investigate gene expression and biological pathways that are altered during disease. There are few studies of the changes in gene expression in EAE, and these have mostly been done in a chronic mouse EAE model. EAE induced in the Lewis with myelin basic protein (MBP-EAE) is well characterised, making it an ideal candidate for the analysis of gene expression in this disease model. Methodology/principal findings MBP-EAE was induced in female Lewis rats by inoculation with MBP and adjuvants. Total RNA was extracted from the spinal cords and used for micro-array analysis using AffimetrixGeneChip Rat Exon 1.0 ST Arrays. Gene expression in the spinal cords was compared between healthy female rats and female rats with MBP-EAE. Gene expression in the spinal cord of rats with MBP-EAE differed from that in the spinal cord of normal rats, and there was regulation of pathways involved with immune function and nervous system function. For selected genes the change in expression was confirmed with real-time PCR. Conclusions/significance EAE leads to modulation of gene expression in the spinal cord. We have identified the genes that are most significantly regulated in MBP-EAE in the Lewis rat and produced a profile of gene expression in the spinal cord at the peak of disease.